Perbedaan Kadar Hemoglobin Sebelum dan Setelah Mengonsumsi Minuman Tradisional Pakombo Pada Masyarakat Penderita Anemia di Wilayah Kecamatan Belo Kabupaten Bima - Eka Atyi Purwasih; Ida Bagus Rai Wiadnya; Thomas Tandi Manu; I Wayan Getas (Poltekkes Kemenkes Mataram, 2025)
Background: Anemia is a condition characterized by a decrease in hemoglobin levels, which can lead to fatigue, weakness, and reduced work productivity. Pakombo is a traditional drink from Bima, believed to help increase hemoglobin levels due to its natural ingredients rich in iron and other essential nutrients. Objective: To determine the difference in hemoglobin levels before and after consuming Pakombo in individuals with anemia in Belo Subdistrict, Bima Regency. Method: This study employed an observational analytic design. The sample consisted of 31 individuals with anemia, selected using a non-random sampling technique. Hemoglobin level measurements were analyzed using the paired t-test. Results: The average hemoglobin level before consuming the traditional beverage Pakombo was 8.74 g/dL, and after consumption, it increased to 10.20 g/dL. The statistical analysis using the paired t-test showed a p-value of 0,000 < (α) 0,05. Conclusion: There is a significant difference in hemoglobin levels before and after consuming the traditional Pakombo drink among individuals with anemia in Belo Subdistrict, Bima Regency.